Using Gamma Ray Radiation to Estimate the Types and Contents of Radioactive Nuclides in Some Ported Sugar Samples, Libya - Hamad Hasan; Raja Amhmmid; Hamdi Khatab; Jamila Ali; Amani Al Kaseh (AlQalam Journal of Medical and Applied Sciences, 2025)
The radioactive nuclides were measured in Sugar samples collected from some Libyan markets by using gamma ray (NaI) detector, the results recorded that all the samples containing different contents and types of radioactive nuclides, their contents were ranged between: The activity concentrations in the sugar samples were fluctuated in the ranges of (17.65 - 48.02), (27.63 - 56.13), (20.92 - 62.34) and (20.45 - 102.93 Bq. Kg−1) for 226Ra, 238 U, 322Th and 40K, respectively. For most samples, the activity concentrations of 226Ra for samples under investigation are higher than those of the world’s population, with an average of (32, 35, and 30 for Ra, U, and Th, respectively) Bq. Kg−1, respectively. For 238U, the activity concentrations of all samples are higher than the permissible level for all samples under investigation (33 and 20) Bq. Kg−1 and 1 Bq.L−1.